1995
DOI: 10.1039/dt9950001649
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenolato complexes of bismuth and antimony. Syntheses, thermolysis reactions, and crystal structure of Sb(SC6H2Pri 3-2,4,6)3

Abstract: Antimony( 111) and bismuth (111) complexes of sterically demanding arenechalcogenolato ligands, M(EC,H,R',-2.4,6), (E = S or Se; M = Sb or Bi; R' = Me, Pri or But) have been prepared by either protolysis of the amides M [N(SiMe,),], with arenechalcogenols, or from MCI, by halide exchange (M = Bi or Sb). The complexes are monomeric in the solid state and sublime readily. The crystal structure of Sb( SC,H2Prl,-2,4,6), has been determined by X-ray diffraction. The compound possesses a trigonal-pyramidal geometry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…In contrast, the use of tailor-made single-source precursors, in which the desired group 15 and group 16 elements are connected by a stable chemical bond and the material composition is ideally pre-formed on the molecular level, for the synthesis of nanostructured M 2 E 3 materials has only been recently demonstrated. [46,47,48,49,50] These studies clearly showed the strong influence of the organic substituents on the decomposition mechanism and formation of the desired material. For instance, Bochmann et al investigated the thermal decomposition of tris-selenolato-stibines and bismuthines of the type M(SeR) 3 .…”
Section: Synthesis Of Binary Nanomaterials Sb 2 E 3 (E = S Se Te) Imentioning
confidence: 92%
See 4 more Smart Citations
“…In contrast, the use of tailor-made single-source precursors, in which the desired group 15 and group 16 elements are connected by a stable chemical bond and the material composition is ideally pre-formed on the molecular level, for the synthesis of nanostructured M 2 E 3 materials has only been recently demonstrated. [46,47,48,49,50] These studies clearly showed the strong influence of the organic substituents on the decomposition mechanism and formation of the desired material. For instance, Bochmann et al investigated the thermal decomposition of tris-selenolato-stibines and bismuthines of the type M(SeR) 3 .…”
Section: Synthesis Of Binary Nanomaterials Sb 2 E 3 (E = S Se Te) Imentioning
confidence: 92%
“…9), [80] Bi(SePh) 3 , [81] and Bi(SeTrip) 3 . [46] M a n u s c r i p t Figure 9. Solid state structure of Sb(SeMe) 3 .…”
Section: Rm(er') 2 (M = Sb Bi; E = Se Te)mentioning
confidence: 98%
See 3 more Smart Citations